2016
DOI: 10.1002/jat.3316
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanisms of action of 2, 2’, 4, 4’‐tetrabromodiphenyl ether (BDE‐47) and its metabolites (5‐OH‐BDE‐47 and 6‐OH‐BDE‐47) on cell proliferation in OVCAR‐3 ovarian cancer cells and MCF‐7 breast cancer cells

Abstract: Data concerning the possible action of polybrominated diphenyl ethers (PBDEs) in hormone-dependent cancer are scarce. Some data showed that PBDEs may directly affect breast cancer cells formation and only one research showed increased proliferation of the OVCAR-3 cells, but the results are ambiguous and the mechanisms are not clear. There is growing evidence that not only parent compounds but also its metabolites may be involved in cancer development. The present study was, therefore, designed to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 65 publications
0
10
1
Order By: Relevance
“…The results of our previous study (Karpeta et al, 2016), showed that BDE-47 increased OVCAR-3 cell proliferation mainly via the activation of cell cycle genes and protein expression and hydroxylated metabolites of BDE-47 stimulated MCF-7 proliferation through genomic action (an increase in cell cycle genes and protein expression, and the downregulation of estrogen receptors) and non-genomic action (the activation of ERK1/2 and PKCα phosphorylation). Data from aforementioned study showed cell-specific action of the parent compound, while a similar effect of metabolites on apoptosis in both OVCAR-3 and MCF-7 cells.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The results of our previous study (Karpeta et al, 2016), showed that BDE-47 increased OVCAR-3 cell proliferation mainly via the activation of cell cycle genes and protein expression and hydroxylated metabolites of BDE-47 stimulated MCF-7 proliferation through genomic action (an increase in cell cycle genes and protein expression, and the downregulation of estrogen receptors) and non-genomic action (the activation of ERK1/2 and PKCα phosphorylation). Data from aforementioned study showed cell-specific action of the parent compound, while a similar effect of metabolites on apoptosis in both OVCAR-3 and MCF-7 cells.…”
Section: Discussionmentioning
confidence: 85%
“…Hydroxylated metabolites of PBDE were found to be potent agonists of estrogen receptors (Kojima et al, ) and thus might affect apoptosis in MCF‐7 cells in a similar way to estradiol. Our previous studies showed that hydroxylated metabolites (5‐OH‐BDE‐47 and 6‐OH‐BDE‐47) increased the estrogen receptor protein expression in OVCAR‐3 and MCF‐7 cells (Karpeta et al, ). Increased expression of estrogen receptors by 5‐OH‐BDE‐47 and 6‐OH‐BDE‐47 increases the number of binding sites for both endogenous and exogenous estrogens suggesting potential carcinogenic action of hydroxylated PBDE metabolites.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations